# 3(y-2x) = 5(y-2x) - 8 -1/3 (x-5y) = (y-x) -4 that is all it says. I am assuming you need to find the value for x and y

*print*Print*list*Cite

### 1 Answer

Solve: `3(y-2x) = 5(y-2x) - 8` --- (i)

`-1/3 (x-5y) = (y-x) -4` --- (ii)

`3(y-2x) = 5(y-2x) - 8` --- (i)

Subtract `3(y-2x)` from both sides,

`0 = 2(y-2x) - 8`

Add 8 to both sides and change sides,

`2(y-2x)= 8`

Divide by 2,

`y-2x=4` --- (iii)

From eqn. (ii), `-1/3 (x-5y) = (y-x) -4 `

Multiply by 3, and apply distributive property

`-x+5y=3y-3x-4`

Subtract `3y-3x` from both sides,

`-x+3x+5y-3y=-4`

`rArr 2x+2y=-4` --- (iv)

(iii)+(iv)

---------------------

`3y=0`

`rArr y=0`

Put the value of `y` in the original equation (ii),

`-1/3(x-5*0)=(0-x)-4`

Add `x` to both sides,

`-1/3x+x=-4`

`rArr 2/3x=-4`

`rArr x=-4*3/2=-6`

Thus the solution to the given set of equations is **x=-6, y=0**.